The Seeds’ Morphological and Anatomical study of four species of Vicia L. - حسن آلاء; دينا حداد; لطيفة علي (Latakia University Journal -Biological Sciences Series, 2024)
The study confirmed that the seeds of the studied species are non-endospermic. The starch and protein deposits are located within the cotyledons, and the starch occupies the largest area of them. The starch grains are characterized by their oval shape and the umbilical hilum is elongated. As for the protein deposits, they form the outer layer of the endosperm and contain simple aleurone grains composed of spherical bodies only. The anatomical study of the seed coat showed that it consists of several layers. The first is the Macrosclereids, which forms two layers at the hilum area and continues as one layer throughout the entire coat, and its cells are arranged in several rows. Next is an area called the Osteosclereids, which consists of one row of cells that is absent at the hilum and continues until the end of the integument, followed by several layers of parenchyma cells. As for the surface of the seed, it was found that it consists of radiate and dark areas in Vicia sativa, while Vicia galeata and Vicia palaestina were distinguished by the presence of veins, and Vicia hybrida was unique in the presence of soft spots and veins, and the papillae were abundant on its surface, which were conical and differed in height, and had wax deposits that were more evident in the specie of Vicia sativa.